Penegakan Hukum terhadap Tindak Pidana Pencurian berdasarkan Putusan Nomor 60/PID.B/2024/PN Amlapura - Ni Ketut Ratih Ganeshwari Jaya; Ni Ketut Wiratny; Ida I Dewa Ayu Dwiyanti (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study examines the enforcement of criminal law in relation to the offense of aggravated theft as adjudicated in the District Court Decision of Amlapura No. 60/PID.B/2024/PN Amlapura, wherein the Defendant, Jana alias Tobi, was found legally and convincingly guilty of committing aggravated theft as stipulated under Article 363 paragraph (1) point 4 of the Indonesian Penal Code (KUHP). The objective of this research is to analyze the application of criminal law in the aforementioned case, with a particular focus on two principal legal issues: (1) how law enforcement was implemented in the case in question, and (2) how the judicial decision aligns with the foundational legal principles of justice, legal certainty, and utility. The research employs a normative juridical method with a descriptive-analytical approach, and utilizes both the theory of law enforcement and the theory of criminal acts as the conceptual framework. The findings indicate that all elements of the criminal offense under Article 363 paragraph (1) point 4 of the Penal Code were fulfilled, and that the panel of judges duly considered both aggravating and mitigating factors in a balanced manner. Nonetheless, further analysis reveals that the Defendant’s role in the commission of the offense was more auxiliary in nature, thereby suggesting that the normative application of Article 55 of the Penal Code would have been more appropriate. This misapplication of legal provisions potentially gives rise to substantive injustice and opens the possibility for further legal remedies. The study concludes that although the formal procedures of law enforcement were conducted in accordance with prevailing legal standards, there exists a substantive deficiency in the identification of the perpetrator’s role, which adversely affects the overall fairness of the verdict. The novelty of this research lies in its critical analysis of the accuracy of judicial application of substantive criminal norms and the imperative of rigorous judicial reasoning in sentencing, aimed at reinforcing the integrity and consistency of the Indonesian criminal justice system.